2017
DOI: 10.1007/s11302-017-9585-0
|View full text |Cite
|
Sign up to set email alerts
|

P2X7R antagonism after subfailure overstretch injury of blood vessels reverses vasomotor dysfunction and prevents apoptosis

Abstract: Human saphenous vein (HSV) is harvested and prepared prior to implantation as an arterial bypass graft. Injury and the response to injury from surgical harvest and preparation trigger cascades of molecular events and contribute to graft remodeling and intimal hyperplasia. Apoptosis is an early response after implantation that contributes the development of neointimal lesions. Here, we showed that surgical harvest and preparation of HSV leads to vasomotor dysfunction, increased apoptosis and downregulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…In addition, lowering Niban expression can lead to upregulation of p21 and induce apoptosis by inhibiting cell cycle and cell proliferation [24]. Studies have also shown that vasomotor dysfunction leads to decreased phosphorylation of anti-apoptotic protein Niban and promotes apoptosis, while recovery and increase of Niban phosphorylation can upregulate the anti-apoptotic protein Akt and reduce caspase 3/7 activities, restoring vasomotor function and inhibiting apoptosis [25]. Further studies demonstrated that Niban is involved in ER stress and induces autophagy by regulating the mTOR pathway to inhibit apoptosis [22,26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lowering Niban expression can lead to upregulation of p21 and induce apoptosis by inhibiting cell cycle and cell proliferation [24]. Studies have also shown that vasomotor dysfunction leads to decreased phosphorylation of anti-apoptotic protein Niban and promotes apoptosis, while recovery and increase of Niban phosphorylation can upregulate the anti-apoptotic protein Akt and reduce caspase 3/7 activities, restoring vasomotor function and inhibiting apoptosis [25]. Further studies demonstrated that Niban is involved in ER stress and induces autophagy by regulating the mTOR pathway to inhibit apoptosis [22,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the antagonists of P2X7R may counteract the effect of P2X7R and have cardioprotective effects during MI/R (Luo et al, ; Tu et al, ). The mechanism underlying the role of P2X7R on the MI/R injury was further suggested to be related to its effects on cardiomyocyte apoptosis (Luo et al, ). In accordance, we also found the P2X7R expression was increased in individually HFD or I/R myocardium; moreover, P2X7R expression in myocardium was even higher in HFD MI/R rats.…”
Section: Discussionmentioning
confidence: 99%
“…IRI is a hallmark not only of organ transplant but also cardiovascular disease, and activation of purinergic signaling is now recognized as a driver of IR‐induced cardiovascular damage as evidenced in various recent studies . Signaling via P2X receptors has been shown to be detrimental in cardiovascular IRI, and blockade of P2X7 receptors reverses vasomotor dysfunction in saphenous vein grafts during coronary artery bypass . Although mainstay antithrombotic therapies act by blocking the P2Y12‐mediated aggregation of platelets, growing evidence has revealed a potential protective role for P2Y receptor signaling in cardiac IRI .…”
Section: Targeting Atp In Iri and Graft Preservationmentioning
confidence: 99%
“…14,36,37 Signaling via P2X receptors has been shown to be detrimental in cardiovascular IRI, and blockade of P2X7 receptors reverses vasomotor dysfunction in saphenous vein grafts during coronary artery bypass. 38 Although mainstay antithrombotic therapies act by blocking the P2Y12-mediated aggregation of platelets, growing evidence has revealed a potential protective role for P2Y receptor signaling in cardiac IRI. 39 Here, direct agonism of P2Y2 receptors by exogenous uridine-5'-triphosphate (UTP) reduces infarct size and functional deficits in a rat model of myocardial infarction, 40 and inhibition of P2Y receptors blocks the protective effects of UTP-mediated purinergic signaling.…”
Section: A3rmentioning
confidence: 99%